Legal Measures for Controlling Fuel Vending Machine Business Operations in Local Government Organizations - Sukperm, Kritiya; Barisri, Jirapon (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2021)
In this research of legal measures for controlling the operations of the fuel vending machine business in local government organizations, the researcher studied the existing legal measures and legal issues to suggest proper guidelines to regulate the operations of the fuel vending machine business in local government organizations. The study found that the local government organizations have adopted the activities of supervision of fuel control businesses in accordance with the Fuel Control Act, B.E. 2542 (1999), which has been in operation since 2003. It was also found that the control of the operations of the fuel vending machine business has not yet been clear on the legal issues concerning safety standards for the life and property of the people in the area. This brought problems and obstacles to the performance of duties of law enforcement officers. For this reason, this research has legal recommendations for the submission of evidence to support the fuel vending machine business notification and for law enforcement officers’ inspection of workplaces including a brief map and a plan for setting up fuel vending machines, business location inspection, land use according to the Town Planning Act. For legal recommendations for the performance of duties, law enforcement officers of local government organizations should set a budget and a plan to inspect vending machine business locations, and should be equipped with technical knowledge to evaluate the business performance.